JPATS 2021
DOI: 10.25259/jpats_22_2020
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uncontrolled asthma among Sudanese adult patients

Abstract: Objectives: Uncontrolled asthma is a major health problem resulting in increased morbidity, mortality, healthcare utilization, and costs. The aim of this study was to determine the level of asthma control and its associated factors in Sudan. Materials and Methods: We performed a cross-sectional study of 362 adult asthmatics consecutively recruited from the three main tertiary hospitals in Khartoum State-Sudan, between March and June 2018. Data were collected using standardized questionnaires and the asthma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous primary studies and reviews reported a high prevalence of uncontrolled asthma in Africa region (45%–90%). 49 , 50 , 51 , 52 In Africa, mortality rates from asthma is disproportionately high. 53 Therefore, emphasis should be given to improve medication adherence among asthmatic patients in Africa through the improvement of the availability, affordability and accessibility of essential medicines used for the treatment of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous primary studies and reviews reported a high prevalence of uncontrolled asthma in Africa region (45%–90%). 49 , 50 , 51 , 52 In Africa, mortality rates from asthma is disproportionately high. 53 Therefore, emphasis should be given to improve medication adherence among asthmatic patients in Africa through the improvement of the availability, affordability and accessibility of essential medicines used for the treatment of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other neighboring countries, these estimates are relatively lower than in Egypt, but similar to the Democratic Republic of Congo [ 76 , 97 ]. In Sudan, asthma is among the top 10 cause of hospitalization, and the rate of uncontrolled disease is very high reaching up to 84.5% according to a recent study from Osman et al [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence is a major factor causing poor control of the disease. Involuntary poor adherence occurs when patients do not use their inhalers correctly ( 18 , 19 ) or have not understood the dosage regimen. Dhadge et al from India found that despite appropriate training, patients made critical mistakes in use of inhalers within the first 24 h which sequentially increased at 7 days and 28 days respectively ( 20 ).…”
Section: Patient Factorsmentioning
confidence: 99%